Treating axial spondyloarthritis and peripheral spondyloarthritis, especially psoriatic arthritis, to target: 2017 update of recommendations by an international task force. Issue 1 (6th July 2017) - Smolen, Josef S; Schöls, Monika; Braun, Jürgen; Dougados, Maxime; FitzGerald, Oliver; Gladman, Dafna D; Kavanaugh, Arthur; Landewé, Robert; Mease, Philip; Sieper, Joachim; Stamm, Tanja; Wit, Maarten de; et al.
Abstract : Therapeutic targets have been defined for axial and peripheral spondyloarthritis (SpA) in 2012, but the evidence for these recommendations was only of indirect nature. These recommendations were re-evaluated in light of new insights. Based on the results of a systematic literature review and expert opinion, a task force of rheumatologists, dermatologists, patients and a health professional developed an update of the 2012 recommendations. These underwent intensive discussions, on site voting and subsequent anonymous electronic voting on levels of agreement with each item. A set of 5 overarching principles and 11 recommendations were developed and voted on. Some items were present in the previous recommendations, while others were significantly changed or newly formulated. The 2017 task force arrived at a single set of recommendations for axial and peripheral SpA, including psoriatic arthritis (PsA). The most exhaustive discussions related to whether PsA should be assessed using unidimensional composite scores for its different domains or multidimensional scores that comprise multiple domains. This question was not resolved and constitutes an important research agenda. There was broad agreement, now better supported by data than in 2012, that remission/inactive disease and, alternatively, low/minimal disease activity are the principal targets for the treatment of PsA. As instruments to assess the patients on the path to the target, the Ankylosing Spondylitis Disease Activity Score (ASDAS) for axial SpA and the Disease Activity index for PSoriatic Arthritis (DAPSA) and Minimal Disease Activity (MDA) for PsA were recommended, although not supported by all. Shared decision-making between the clinician and the patient was seen as pivotal to the process. The task force defined the treatment target for SpA as remission or low disease activity and developed a large research agenda to further advance the field.